Intonational unity as an integration factor of idea (on the example of Hennady Liashenko’s Second Concerto for Cello and Orchestra) - Tormakhova, Anastasiia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study. The second concert for cello and orchestra by Gennady Lyashenko acts as a model of a work that combines the achievements of modern composer thinking, an extremely profound philosophical meaning and an intimate lyric type of expression. One of the integrating factors of the concert is intonational unity. The disclosure of the specifics of the implementation of this principle on the example of G. Lyashenko’s work is a topical research that will not only help to shape the notion of the specifics of his compositional individual style, but can also become a kind of guidebook for future generations of creators. Main objective of the study is to highlight the role of intonation unity as the factor of the integration of the idea, on the example of the Second Concerto for cello and orchestra G. I. Lyashenko. The research methods are about analyzing the intonational structure of the concerto for cello and orchestra. How the study was done The main leitcomplex and the pathways of its growth are identified and tracked in all sections of the work. Results and conclusions. In the Second concert for cello and orchestra by G. Lyashenko, the main intonation core, taking into account its transformations, has considerable flexibility, appealing to the already established genre and stylistic "signs" of musical thinking. If the intonation in the concert is a factor of the temporal and semantic integration of the work, then the textural, mood-harmonic, orchestral and stylistic devices are the factors of differentiation in the respective areas. This is a unique example of a musical idea, where intonational unity is the central semantic factor in relation to other aspects of musical thinking. Practical significance. Taking into account a strong connection with the traditions that have developed in the national composers’ school in domestic art practice combining with personal creative methods, makes the highlighting of the potential of the intonational unity, as an integration factor, is considered a promising approach worthy of imitation.